(untitled) (TAMADDUN NURI JURNALI, 2025)
This article examines the essence of intellectuality and its role in the spiritual and moral development of society. It is emphasized that the maturity of a person is determined by the level of intelligence, which is formed through his theoretical knowledge and practical experience acquired in the process of self-development. Particular attention is paid to the relationship between intelligence and professional activity, worldview and moral and ethical values.